Relation between Fatigue Limit and Tensile Strength at Different Tempering Temperature and Time of Ck55 Steel - R.Biswal, S.; T.Nayak, S. (International Journal of Engineering and Technology, 2018)
Fatigue properties of tempered Ck55 (.55%C) has been investigated by using Moore rotating beam testing machine at a load ratio of R = -1 and cycling frequency of 100 Hz with specific consideration regarding micro structural points of interest. Ck55 steels demonstrate a distinct variation of fatigue limit and life at different tempering temperature and time length. No specimen failed below fatigue limit for high number of cycles.Â The actual fatigue test results for given materials, relates the tempering temperature and time which is because of the formation and changes in the microstructure. An attempt has been made to imperative connections between tensile strength and endurance life by varying tempering temperature and time.Â